Serum cytokines as a biomarker for immune checkpoint inhibitor toxicity in patients with pleural mesothelioma - Farooqi, Saima Jamil; Zhao, Zhi; Öjlert, Åsa Kristina; Thunold, Solfrid; Juul, Hedvig Vidarsdotter; Bjaanæs, Maria Moksnes; Horndalsveen, Henrik; Nymoen, Hanne Marte Gjertsen; Helland, Åslaug; Haakensen, Vilde Drageset (Frontiers in Immunology, 2024)
BackgroundPleural mesothelioma (PM) is a rare cancer with a dismal prognosis. Dual immune checkpoint inhibitors have improved overall survival, but the rate of immune-related adverse events (irAEs) is high. Serum cytokines reflect systemic immune reactions and may serve as biomarkers for irAEs.Patients and methodsPatients with pleural mesothelioma treated with nivolumab and ipilimumab with or without UV1 vaccine in the NIPU study were included. Serum cytokine levels were measured by Bio-Plex Pro Human Cytokine Screening 48-Plex Panel Assay. Correlations between cytokine levels and irAEs were analyzed by generalized linear mixed models to identify potential diagnostic and predictive biomarkers.ResultsHigher levels of MIG, eotaxin, MIP-1α, IP-10, TNF-α, MIP-1β, IL-4, MIF, IL-16, IL-2RA, SCGF.β and PDFG-BB at baseline are associated with increased risk of developing one or more irAEs. In particular, higher baseline levels of MIG are positively associated with thyroiditis and hypophysitis, and elevated levels of IP-10 and MIG to dermatitis. During the course of treatment, higher levels of MIG, eotaxin, MIF, TNF-α, MIP-1β, IL-4 and IL-16 are associated with an ongoing irAE. We found both predictive and diagnostic value of MIF with fatigue and of eotaxin with both colitis and pneumonitis. Higher levels of CTACK is associated with a lower risk of developing hepatitis, both before and after treatment.ConclusionsElevated levels of certain cytokines, both before and after onset of treatment, correlate with specific irAEs in PM patients receiving ICIs. These cytokines may be used as biomarkers to predict and detect irAES.